Ten days of supplementation with a standardized Boswellia serrata extract attenuates soreness and accelerates recovery after repeated bouts of downhill running in recreationally active men - Dawna Salter; Himana Yalamanchi; Aiswarya Yalamanchi; Amulya Yalamanchi (Frontiers in Sports and Active Living)
Extracts derived from Indian frankincense (Boswellia serrata) effectively reduce the pain and swelling associated with osteoarthritis. It is unknown whether the anti-inflammatory and analgesic properties of B. serrata extend to muscle and joint pain resulting from high-impact eccentric exercise. This pilot study evaluated the efficacy of a standardized B. serrata extract LI51202F1 (SBS) to decrease soreness and improve recovery after repeated bouts of downhill running (DHR) compared to placebo (PLA). In total, 50 men (mean age 28 ± 4) were randomly allocated to consume 60 mg SBS or PLA once per day for 10 days (6 days before, the day of, and 3 days after DHR). On day 7, delayed soreness was induced by three 15-min DHR episodes on a 10% declined treadmill. Visual analog scale (VAS) scores of joint and muscle soreness, in addition to the maximal weight lifted for a one-repetition leg extension (1RM-LE) were assessed at baseline (pre-supplementation) and on days 8, 9, and 10. Blood and urine samples collected at baseline, before, and after DHR were analyzed for inflammation-related biomarkers. VAS scores significantly increased while muscle strength decreased from baseline measures after DHR regardless of group assignment (main effect of time p < 0.001). However, the subjects who received the supplement reported reduced muscle soreness on days 8, 9, and 10 compared to those who received the PLA. On day 9, peak soreness scores were lower in the SBS group than in the PLA group (p = 0.001). On day 10, the SBS group’s VAS scores were 8.0 ± 1.6 mm lower than the PLA group (p < 0.001). Supplementation improved recovery time as the 1RM-LE returned to baseline strength by day 10, with the subjects who received the supplement lifting 3.4 ± 1.2 kg more than the PLA group (p = 0.006). The SBS-supplemented subjects reported less knee joint pain after DHR than the PLA group (p < 0.05 on days 8, 9, and 10). C-reactive protein and interleukin-6 increased after DHR, but by day 10, SBS reduced these markers compared to the PLA (p < 0.05). This study suggests that SBS, a novel, standardized extract derived from the gum resin of B. serrata, improves recovery and reduces soreness following high-impact eccentric exercise.Clinical Trial Registrationhttps://ctri.nic.in/Clinicaltrials/pubview2.php, Clinical Trial Registry of India (CTRI/2019/07/020323).